(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
Floating gardening acts as a fruitful climate-change adaptation strategy in different wetland areas of Bangladesh. The study accomplished to examine the profitability of floating gardening in Gopalgonj district of Bangladesh in 2018. A total of 100 floating gardeners were interviewed to achieve the objectives. Descriptive statistics and Cobb-Douglas production function were used to investigate the factors influencing yield of floating gardening. The findings reveal that, small and marginal farmers were more involved in floating gardening. Around sixty-five percent of the production costs was contributed by human labour. Floating gardeners of the study area earned a net return of BDT 457,901 per hectare per year. Human labour, fertilizers and support materials significantly affected the yield. More training and improved marketing system could further enhance the profitability. Int. J. Agril. Res. Innov. Tech. 10(1): 87-93, June 2020